Sustainability of Product Halal in the Postmarket Phase from the Perspective of Islamic Law in Indonesia - Thalhah, Thalhah; Hamizar, Arizal; Hunsouw, M. Taib (STAINI Press, 2025)
This research aims to analyze the assurance of halal products in Indonesia, particularly within the context of Islamic law in the postmarket phase. The study focuses on understanding how existing regulations are capable of providing legal protection for Muslim consumers and ensuring the halal status of products throughout the entire distribution process, from production to consumption. The method used is normative research with a legislative approach, a conceptual approach, and a historical approach. This research examines various regulations related to halal product assurance, including the Halal Product Assurance Law and other related regulations, and analyzes the consistency and implementation of these regulations within the context of Islamic law. The findings of the research indicate that although Indonesia has strong enough regulations to ensure the halal status of products, implementation in the postmarket phase still faces significant challenges. The monitoring of products already circulating in the market has not been fully effective, and there are gaps in the synchronization of existing regulations. From the perspective of Islamic law, halal assurance must cover the entire product life cycle, and therefore, more proactive monitoring and better synergy among related institutions are needed to ensure the sustainability of halal products in Indonesia.